Pengaruh Perubahan Waktu Gilir Kerja Terhadap Kinerja Karyawan Dengan Moderasi Variabel Komitmen Organisasi - Chindy Claudia Rambu Rauna; Survival; Tuti Hastuti (Bulletin of Management and Business, 2023)
The objective of this study was to determine the Effect of Changes in Shift Work as the Impact of the Covid 19 Pandemic on Employee Performance with Organizational Commitment as a Moderating Variable” (Study on Employees of BBPMPPV BOE Malang). The population in this study were employees of BBPMPPV BOE Malang. The sampling technique in this study uses non probability sampling, and the sampling method in this study is total sampling or census. Respondents in this study were 72. The data was processed through Smart Partial Least Square (PLS) software. The results showed that shift time has an influence on employee performance. Organizational commitment has an influence on employee performance. Organizational commitment plays a role in moderating the relationship between shift time and employee performance.